Classification of lumbopelvic-hip complex instability on kinematics amongst female team handball athletes - Gilmer, G. G.; Gascon, S. S.; Oliver, G. D. (Journal of Science and Medicine in Sport, 2018)
Objectives: The purpose of this study was to examine how lumbopelvic-hip complex (LPHC) stability, via knee valgus, affects throwing kinematics during a team handball jump shot. Design: LPHC stability was classified using the value of knee valgus at the instant of landing from the jump shot. If a participant displayed knee valgus of 17° or greater, they were classified as LPHC unstable. Stable and unstable athletes` throwing mechanics were compared. Methods: Twenty female team handball athletes (26.5 ± 4.7 years; 1.75 ± 0.04 m; 74.4 ± 6.4 kg; experience level: 4.8 ± 4.1 years) participated. An electromagnetic tracking system was used to collect kinematic data while participants performed three 9-m jump shots. The variables considered were kinematics of the pelvis, trunk, and shoulder; and segmental speeds of the pelvis, torso, humeral, forearm, and ball velocities. Data were analyzed across four events: foot contact, maximum shoulder external rotation, ball release, and maximum shoulder internal rotation. Results: Statistically significant differences were found between groups in pelvis, trunk, humerus, and forearm velocities at all events (p = 0.05). Specifically, the unstable group displayed significantly slower speeds. Conclusions: These findings suggest the difference in throwing mechanics are affected by LPHC instability for this select group of female team handball athletes. These differences infer an increased risk of injury in the upper and lower extremities when landing from a jump shot because of the energy losses throughout the kinetic chain and lack of utilization of the entire chain. It is recommended that further investigations also consider muscle activation throughout the throwing motion.